Actuator design for arc welding robot - Verma, Anurag; Gor, MM (Kathmandu University Journal of Science, Engineering and Technology, 2010)
The present work is an attempt to determine torque required at each joint of 6-Degree of Freedom Arc Welding Robot for typical horizontal fillet welding operation which will be useful for designing actuator. Here, range of welding speed 90mm/min & 2000mm/min is taken. Result obtained at the end of this analysis will be useful for designing actuator capacity for typical application. The methodology adopted for analysis includes development of dynamic model, determination of velocity and acceleration with respect to time and thus determination of torque using velocity-acceleration and dynamic model. Keywords: Inverse Dynamic Analysis; Lagrange-Euler formulation; Arc Welding Robot DOI: 10.3126/kuset.v6i2.4011 Kathmandu University Journal of Science, Engineering and Technology Vol.6. No II, November, 2010, pp.48-53